2019
DOI: 10.1002/ccd.28629
|View full text |Cite
|
Sign up to set email alerts
|

Reduced radiation exposure in the cardiac catheterization laboratory with a novel vertical radiation shield

Abstract: ObjectivesInvestigation of novel vertical radiation shield (VRS) in reducing operator radiation exposure.BackgroundRadiation exposure to the operator remains an occupational health hazard in the cardiac catheterization laboratory (CCL).MethodsA mannequin simulating an operator was placed near a computational phantom, simulating a patient. Measurement of dose equivalent and Air Kerma located the angle with the highest radiation, followed by a common magnification (8 in.) and comparison of horizontal radiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Multiple randomized trials found less radiation with left versus right radial [45][46][47][48][49] although one trial found more radiation with left radial [50]. Avoiding steep angles, particularly LAO -Caudal, lower magnification, lower frame rate with fluoroscopy, and distance is recommended [51,52]. Further research comparing access sites is warranted to better understand with current technology the risks of radiation exposure.…”
Section: Areas Of Researchmentioning
confidence: 99%
“…Multiple randomized trials found less radiation with left versus right radial [45][46][47][48][49] although one trial found more radiation with left radial [50]. Avoiding steep angles, particularly LAO -Caudal, lower magnification, lower frame rate with fluoroscopy, and distance is recommended [51,52]. Further research comparing access sites is warranted to better understand with current technology the risks of radiation exposure.…”
Section: Areas Of Researchmentioning
confidence: 99%
“…These include avoiding left anterior oblique (LAO) and steep caudal/cranial angulation, greater distance from the X-ray tube, lead shielding, suspended protection systems, and vascular robotics. 6 X-ray generation occurs in an evacuated glass envelope containing a cathode filament and an anode. 7 The cathode filament is heated, and a high voltage is applied across the gap between the cathode and anode causing the cathode to emit electrons that release energy when they strike the anode.…”
Section: Introductionmentioning
confidence: 99%
“…Barium sulfate (BaSO 4 ), bismuth, and tungsten are the most frequently used eco-friendly shielding materials [3]. Numerous studies have been conducted on the shielding performance and manufacturing process technology of these materials, and products using these materials are currently being used in medical institutions [4,5].…”
Section: Introductionmentioning
confidence: 99%